2013
DOI: 10.1007/s00726-013-1550-9
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodeling by polyamines and polyamine analogs

Abstract: Natural polyamines are involved in many molecular processes, including maintenance of DNA structure and RNA processing and translation. Our aim here is to present an overview of the literature concerning the significance of polyamines in the modulation of chromatin arrangement and the transcriptional regulation of gene expression. The pleiotropic picture emerging from the published data highlights that these polycations take part in apparently diverging effects, possibly depending on the heterogeneous experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 62 publications
1
37
0
1
Order By: Relevance
“…It can be argued that increased PA accumulation in response to short-term stress affects the epigenetic modifications of DNA and histones because of their ability to interact with chromatin (Pasini et al, 2014 and references therein). Important aspects of this premise would include: (i) a fundamental role for PAs in epigenetic changes that normally occur in the life of an organism through specific interactions with DNA prior to or during methylation (Krichevsky et al, 2007; Sharma et al, 2012), and (ii) the enhancement of specific epigenetic changes occurring under conditions of priming for stress (cold or salt treatment of seeds during germination to develop tolerance, desiccation of seeds and buds during dormancy, etc.…”
Section: Polyamines and Stress Memory/primingmentioning
confidence: 99%
“…It can be argued that increased PA accumulation in response to short-term stress affects the epigenetic modifications of DNA and histones because of their ability to interact with chromatin (Pasini et al, 2014 and references therein). Important aspects of this premise would include: (i) a fundamental role for PAs in epigenetic changes that normally occur in the life of an organism through specific interactions with DNA prior to or during methylation (Krichevsky et al, 2007; Sharma et al, 2012), and (ii) the enhancement of specific epigenetic changes occurring under conditions of priming for stress (cold or salt treatment of seeds during germination to develop tolerance, desiccation of seeds and buds during dormancy, etc.…”
Section: Polyamines and Stress Memory/primingmentioning
confidence: 99%
“…In all eukaryotic cells, the polyamines are involved in a large number of fundamental biological processes, such as in the regulation of cell proliferation, differentiation and death (Wallace et al 2003; Palmer and Wallace 2010; Traquete et al 2013). Although all of the exact roles of polyamines in these processes are not known, the capacity to interact with DNA and affect DNA conformation are thought to play a role in their normal cellular function (Iacomino and Picariello 1823; Pasini et al 2013). Polyamine pools are in general higher in malignant tissue than in normal tissue (Pegg 1988; Traquete et al 2013), which has suggested the polyamine metabolic pathway as a target for anticancer therapy (Pegg 1988; Seiler 2005; Casero and Woster 2009; Palmer and Wallace 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The papers project the role of polyamines in cell growth and differentiation, cell cycle regulation, gene expression and signal transduction in animals, plants and microorganisms as well as in several pathophysiological processes including carcinogenesis and other diseases. Recently, the significance of polyamines in cell proliferation and carcinogenesis has stimulated further research interest in their biochemical and metabolic regulation at genomic level (Zhu et al 2012;Cervelli et al 2013;Murray-Stewart et al 2013;Pasini et al 2013). Inhibition of polyamine biosynthesis as an antitumor strategy has been demonstrated to be generally ineffective in clinical trials, but there is some potential in human diseases like cancer (Raj et al 2013) and parasitic diseases (Bacchi et al 2009;Preeti et al 2013;von Koschitzky and Kaiser 2013).…”
Section: Prefacementioning
confidence: 99%
“…DNA methylation and covalent modification of histones collaborate to function as epigenetic regulators of gene expression. Pasini et al (2013) offer an overview of the literature regarding polyamine influence on the modulation of chromatin arrangement participating into the transcriptional regulation of gene expression. Polyamine derivatives acting as epigenetic modulators are also presented since these novel polyamine-based pharmacologically active molecules are promising tools in anticancer therapy.…”
Section: Editorialmentioning
confidence: 99%